Evodiamine Prevents Isoproterenol-Induced Cardiac Fibrosis by Regulating Endothelial-to-Mesenchymal Transition - Jiang, Xiao-han; Wu, Qing-qing; Xiao, Yang; Yuan, Yuan; Yang, Zheng; Bian, Zhou-yan; Chang, Wei; Tang, Qi-zhu (Planta Medica, 2017)
Evodiamine, a major component of Evodia rutaecarpa, can protect the myocardium against injury induced by atherosclerosis and ischemia-reperfusion. However, the effect of evodiamine against cardiac fibrosis remains unclear. This study aims to investigate the possible effect and mechanism involved in the function of evodiamine on isoproterenol-induced cardiac fibrosis and endothelial-to-mesenchymal transition. Isoproterenol was used to induce cardiac fibrosis in mice, and evodiamine was gavaged simultaneously. After 14 days, cardiac function was accessed by echocardiography. The extent of cardiac fibrosis and hypertrophy was evaluated by pathological and molecular analyses. The extent of endothelial-to-mesenchymal transition was evaluated by the expression levels of CD31, CD34, α-smooth muscle actin, and vimentin by immunofluorescence staining and Western blot analysis. After 14 days, the heart weight/body weight ratio and heart weight/tibia length ratio revealed no significant difference between the isoproterenol group and the isoproterenol/evodiamine-treated groups, whereas the increased heart weight was reduced in the isoproterenol/evodiamine-treated groups. Echocardiography revealed that interventricular septal thickness and left ventricular posterior wall thickness at the end diastole decreased in the evodiamine-treated groups. Evodiamine reduced isoproterenol-induced cardiac fibrosis as accessed by normalization in collagen deposition and gene expression of hypertrophic and fibrotic markers. Evodiamine also prevented endothelial-to-mesenchymal transition as evidenced by the increased expression levels of CD31 and CD34, decreased expression levels of α-smooth muscle actin and vimentin, and increased microvascular density in the isoproterenol/evodiamine-treated mice hearts. Furthermore, isoproterenol-induced activation of transforming growth factor-β1/Smad signal was also blunted by evodiamine. Therefore, evodiamine may prevent isoproterenol-induced cardiac fibrosis by regulating endothelial-to-mesenchymal transition, which is probably mediated by the blockage of the transforming growth factor-β1/Smad pathway.
Keywords: evodiamine; Evodia rutaecarpa; Rutaceae; cardiac fibrosis; endothelial-to-mesenchymal transition; isoproterenol